Implementasi Sistem Bagi Hasil Tabungan Easy Mudharabah Berdasarkan PSAK 405 Pada Bank Syariah Indonesia Kantor Cabang Cimahi - Ariani Putri Utami; Mia Lasmi Wardiyah (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study examines how the profit-sharing system is implemented in the Easy Mudharabah Savings product at Bank Syariah Indonesia (BSI) Cimahi Branch Office in accordance with Statement of Financial Accounting Standards (PSAK) 405 about Mudharabah Accounting. This study combined field observation and literature review in a descriptive qualitative manner. Interviews, documents, and literature reviews on the National Sharia Council's (DSN-MUI) fatwa on the mudharabah contract were used to gather the data. The findings demonstrate that the Easy Mudharabah Savings program at the BSI Cimahi Branch has been appropriately and sharia-compliantly executed in conformity with PSAK 405 regulations. Customer deposits, as opposed to the bank's permanent liabilities, are recorded as Temporary Syirkah Funds. Based on the agreed-upon nisbah and the average daily balances of the clients, the profit-sharing method is used to calculate the profit-sharing. Furthermore, PSAK 405 is followed in the presentation and disclosure of financial statements, while there is still opportunity to further customer information transparency. All things considered, the results of this study show that the Islamic banking profit-sharing system's implementation of PSAK 405 upholds the values of equity, cooperation, and openness.